Inovasi Nasi Uduk Pandan Wangi (Pandanus amaryllifolius) Instan dengan Penambahan Puree Kacang Merah - Minggrit Diajeng Putri Kusuma; Lilis Sulandari; Niken Purwidiani; Ila Huda Puspita D (Indo-MathEdu Intellectuals Journal, 2026)
The development of food products today is not only directed at ease of preparation, but also at increasing nutritional value to meet the public's need for practical food. This study aims to determine the effect of adding red bean puree on the organoleptic characteristics of instant fragrant pandan uduk rice and determine the best treatment. The study used an experimental method with the addition of red bean puree at 20%, 30%, and 40%. Organoleptic tests were conducted on raw and cooked instant rice by 35 panelists consisting of 5 trained panelists and 30 semi-trained panelists. Assessments included color, grain shape, texture, aroma, taste, and overall preference. Data were analyzed using One-Way ANOVA with the help of SPSS and continued with Duncan's test if there was a significant difference (p < 0.05). The results showed that the addition of red bean puree significantly affected the color and shape of raw rice grains and the color of cooked rice. The best treatment was obtained with the addition of 20% red bean puree with the characteristics of a fairly dominant green color, soft texture, distinctive pandan aroma, and the highest level of preference. The product in the best treatment had a total energy of 136.34 kcal/100 g and 3.28% protein, so the addition of 20% red bean puree produced the most preferred organoleptic characteristics.